The Locked Door - McFadden, Freida (Naperville, Illinois : Poisoned Pen Press, 2023)
"While eleven-year-old Nora Davis was up in her bedroom doing homework, she had no idea her father was killing women in the basement. Until the day the police arrived at their front door. Decades later, Noras father is spending his life behind bars, and Nora is a successful surgeon with a quiet, solitary existence. Nobody knows her father was a notorious serial killer. And she intends to keep it that way. Then Nora discovers one of her young female patients has been murdered. In the same unique and horrific manner that her father used to kill his victims. Somebody knows who Nora is. Somebody wants her to take the fall for this unthinkable crime. But shes not a killer like her father. The police cant pin anything on her. As long as they dont look in her basement"--
Keywords: Serial murderers -- Fiction; Fathers and daughters -- Fiction; Copycat crimes -- Fiction; Psychological fiction; Thrillers (Fiction); Novels